Stereodivergent dehydrative allylation of β-keto esters using a Ru/Pd synergistic catalyst - Thien Phuc Le; Shinji Tanaka; Masahiro Yoshimura; Kazuhiko Sato; Masato Kitamura (Nature Communications, 2022)
α-Alkylation of β-keto esters is a frequently used reaction for carbon–carbon bond formation, but a general, stereoselective version of this reaction is challenging to realize. Here, the authors report a combined ruthenium and palladium catalytic system for the asymmetric dehydrative condensation between cinnamyl-type allylic alcohols and β-keto esters.